Viewing Female Depiction in Frozen 2 - Putri, Tia Aprilianti (Universitas Negeri Semarang, 2021)
Disney is one of the biggest animation companies in the world. They have released many animations since then until now. One of the most popular animations is the princess series. Until 20202, Disney has released fourteen princesses fromÃ‚Â Snow White and the Seven DwarfsÃ‚Â toÃ‚Â Frozen 2. Gender role depictions of the female character(s) were examined with a focus on their behavioral characteristics in the films. The English subtitle ofÃ‚Â Frozen 2Ã‚Â was used to find out the attitudinal expressions about the female characters. In order to make the research easier and more accurate, a concordance tool namedÃ‚Â AntconcÃ‚Â was used to collect the data and create a corpus. Results found that the most recent princess series entitledÃ‚Â Frozen 2Ã‚Â showed the female characters depicted as a precious person who was willing to sacrifice herself for others, kind, heroic, fearless, and full-of-spirit. However, Disney also depicted the female characters as liar and trouble maker. In this case, Disney keeps showing that females cannot be seen using the traditional genderÃ¢â‚¬â„¢s perspective anymore. A Female is not only feminine, but she also can be masculine as a man.